Asteroid lightcurve inversion with Lommel–Seeliger ellipsoids. (1st December 2015) - Muinonen, Karri; Wilkman, Olli; Cellino, Alberto; Wang, Xiaobin; Wang, Yibo
Abstract: We derive initial rotation, shape, and scattering properties for asteroids from sparse and dense photometry based on the so-called Lommel–Seeliger ellipsoid (LS ellipsoid). Due to the analytical disk-integrated brightness, the LS ellipsoid allows for fast rotation-period, pole-orientation, and shape analyses, as well as efficient Markov-chain Monte Carlo solutions (MCMC). We apply the methods to simulated sparse Gaia photometry, as well as to ground-based photometry composed of dense lightcurves. For a specific Gaia simulation, we make use of a numerical reflection coefficient developed for particulate surfaces, and utilize the LS ellipsoid in the inversion of the simulated data. We conclude that, in a majority of cases, initial LS ellipsoid retrieval of the parameters is satisfactory. Finally, we formulate a single-scattering phase function that, for a spherical asteroid, results in the H, G 1, G 2 photometric phase function. Abstract : Highlights: Lommel-Seeliger ellipsoid enables statistical asteroid lightcurve inversion. Efficient Markov-chain Monte Carlo methods are introduced for lightcurves. Methods are successfully applied to dense ground-based data. Sparse simulated Gaia data are successfully assessed with the methods.